Nivel de conocimiento y prácticas del apego precoz, como normativa del establecimiento amigo de la madre y el niño (esamyn) en el hospital león becerra de milagro periodo mayo-septiembre 2019. - Alvarado Jordan, Melany Alexandra (2019)
The current research work is part of the explanatory work of several bibliographic citations that are important to express about the benefits of early attachment, and to know on this topic the level of knowledge that pregnant women at the León Becerra de Milagro Hospital have. To highlight this research project, extensive research on early attachment and the steps taken by the establishment established by the mother and child friend (ESAMyN). Also to know how an emotional bond can be given that favors both as well as postpartum depression, thermoregulation and decreased crying in the baby. So that this project was verified by means of the instruments applied as well as the observation and survey form that was obtained to 56 mothers and 20 specified personnel, so that these results could be provided in graphic cakes with their respective analysis and interpretation.